The failed assumptions of some social scientists on the role of religion in international relations - Shuriye, Abdi Omar (Centre for Promoting Ideas, USA, 2011)
After decades of overwhelming domination of certain conventional actors in international relations religion is now a contending actor in international politics. In fact, religion is increasingly becoming essential element in domestic affairs of the state level as well as in the international affairs of contemporary global politics. This research therefore, is an attempt to display the failed assumptions of Western social scientists on the role of religion in international relations.